PERANCANGAN PENGELOLAAN DATA SANGGAR SENI SAAYUN SALANGKAH KOTA BUKITTINGGI - Febby Kesumaningtyas; Wizra Aulia; Muhamad Ravi Farhan (Sekolah Tinggi Teknologi Industri Padang, 2022)
The design of Data Management for the SaayunSalapak Art Studio serves to design an application that is expected to support the management of art gallery data, member registration and studio event schedule data which is intended to make it easy for members to get the information needed by studio members and make it easier for admins to manage schedule of events, decision making and by utilizing web programming as application software is expected to replace ways that are less effective and efficient and are expected to facilitate reporting on the results of the decision making process. Design and manufacture of data processing applications using the System Development Life Cycle (SDLC) method. Starting from problem identification, design, modeling to implementation.